The Influence of Teacher Competency on Students' Learning Interest - Umam, Khoirul; Sulaeman, Maryam; Marlina, Yuli (EDUTEC : Journal of Education And Technology, 2024)
The educational sector, particularly in the role of teachers as educators, has not fully met the expectations required for teachers to demonstrate field-specific competence that aligns with national education goals. These goals emphasize cultivating students who exhibit both achievement and character, contributing to the pride of their community, nation, and state. This study aims to analyze the impact of teacher competency on students' interest in learning, quantify the extent of this influence, and explore methods to enhance student interest through improved teacher competency. The research employs a descriptive analysis approach, using random sampling and data collection techniques such as observation and documentation. Data analysis is conducted using the product-moment correlation method. The results indicate a correlation coefficient of 0.785 (78.5%) and a determination coefficient of 0.617 (61.7%), demonstrating a significant positive relationship between teacher competency and students’ learning interest.